Current status and clinical association of beta-catenin with juvenile nasopharyngeal angiofibroma. Issue 10 (30th August 2016) - Mishra, A; Singh, V; Verma, V; Pandey, S; Trivedi, R; Singh, H P; Kumar, S; Dwivedi, R C; Mishra, S C
Abstract: Objective: A possible role of the APC/beta-catenin pathway in the pathogenesis of sporadic juvenile nasopharyngeal angiofibroma has been suggested. This paper presents its current status and clinical association in our patients. Method: A prospective observational study was conducted at King George Medical University and Central Drug Research Institute, in Lucknow, India. Western blot analysis was undertaken in 16 cases to examine beta-catenin expression. The clinical details were recorded along with follow up observations, to determine associations. Results: Up-regulation of beta-catenin expression was seen in 69 per cent of cases. The clinical variables did not reveal significant differences between patients with extremes of expression (extreme under- vs over-expression). However, absent expression was shown exclusively in young adults aged over 18 years, while enhanced expression was associated with an altered facial profile. Conclusion: Although a beta-catenin association was seen in a subset of our sporadic juvenile nasopharyngeal angiofibroma cases, its expression was not homogeneous. This is in contrast to the Western literature that suggests a universal (homogenous) enhanced expression in the majority. Hence, further research is required to better define its molecular cascade.